Isolation of verotoxigenic Escherichia coli O157 from poultry - Pilipcinec, E; Tkáciková, L; Naas, H T; Cabadaj, R; Mikula, I (Folia microbiologica, 1999)
Results obtained by examination of cloacal swabs from poultry for the presence of verotoxigenic strains of E. coli O157:H7 are presented. Twenty samples (9.2%) of 216 samples examined were positive for E. coli O157. Out of 20 E. coli O157, 19 strains were positive for the production of both verotoxins (VT1 and VT2). However, none of them was positive for the presence of H7 antigen.
Keywords: kur domácí; shiga toxiny; Shiga Toxins; Escherichia coli Infections; Chickens; Disease Reservoirs; Animals; Foodborne Diseases; lidé; nemoci přenášené potravou; zdroje nemoci; Food Microbiology; Humans; infekce vyvolané Escherichia coli; zvířata; Escherichia coli O157; potravinářská mikrobiologie